2019
DOI: 10.1111/mec.14986
|View full text |Cite|
|
Sign up to set email alerts
|

The genomic basis of adaptation to high‐altitude habitats in the eastern honey bee (Apis cerana)

Abstract: The eastern honey bee (Apis cerana) is of central importance for agriculture in Asia. It has adapted to a wide variety of environmental conditions across its native range in southern and eastern Asia, which includes high‐altitude regions. eastern honey bees inhabiting mountains differ morphologically from neighbouring lowland populations and may also exhibit differences in physiology and behaviour. We compared the genomes of 60 eastern honey bees collected from high and low altitudes in Yunnan and Gansu provin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 82 publications
(102 reference statements)
4
45
0
Order By: Relevance
“…However, insulin signalling is involved in other processes such as the sleep cycle, longevity, and sexual maturation, any of which may respond to aspects of seasonality that correlate with Isothermality (Cong et al, ; Post et al, ) . Although limited in number, other studies of montane adaptation in bees have suggested that the strongest signatures of selection may be in genes associated with olfaction, foraging, and reproduction (Montero‐Mendieta et al, ; Wallberg et al, ). Honey bees from Kenyan elevation gradients show an adaptive sweep in a high‐elevation inversion that contains several genes, but most notably several octopamine receptors (Wallberg et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, insulin signalling is involved in other processes such as the sleep cycle, longevity, and sexual maturation, any of which may respond to aspects of seasonality that correlate with Isothermality (Cong et al, ; Post et al, ) . Although limited in number, other studies of montane adaptation in bees have suggested that the strongest signatures of selection may be in genes associated with olfaction, foraging, and reproduction (Montero‐Mendieta et al, ; Wallberg et al, ). Honey bees from Kenyan elevation gradients show an adaptive sweep in a high‐elevation inversion that contains several genes, but most notably several octopamine receptors (Wallberg et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Unsaturated fatty acids in the membrane can increase membrane fluidity, causing higher cold tolerance (Brown et al, 2019;Haubert et al, 2008;Ohtsu et al, 1998). Furthermore, in two studies on honey bees and bumble bees (Jackson et al, 2020;Montero-Mendieta et al, 2019), other potassium channels were detected as potential outlier loci in relation to altitude. Four out of the remaining six loci with known function encode housekeeping proteins (Table 4).…”
Section: Altitudinal Adaptationmentioning
confidence: 99%
“…The selection pressure on other genes such as the leucokinin and NMDA receptors was hypothesized to mediate foraging in adaptation to highland habitats (Montero-Mendieta et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Population genomics of A.cerana also facilitate the acquisition of data for the identification of genes involved in the adaptative evolution of A. cerana . A study comparing 60 eastern honeybee samples from differing altitudes in Yunan Province identified 37 genes under positive selection at higher altitudes (Montero‐Mendieta et al., 2019). Among these genes, the selection pressure on the esterase FE4‐like gene in highland A. cerana is thought to play a role in the regulation of metabolic activity at lower temperatures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation